2016
DOI: 10.2135/cropsci2015.07.0445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Photoperiod on Time to Flowering in Chickpea

Abstract: Flowering time is a key factor in determining the adaptation of crops to diverse environments. Temperature and photoperiod are the two major environmental variables that affect the length of the period between sowing and flowering and the rate of plant development. The objectives of this research were to examine the days to flowering of selected chickpea (Cicer arietinum L.) accessions grown in a range of thermal regimes combined with either long or short days and to examine the interaction between photoperiod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The two high yielding accessions developed and released by the Crop Development Centre, University of Saskatchewan [CDC Corinne (S1) and CDC Frontier (S2)] ( Warkentin et al, 2005 ; Tar’an et al, 2009 ) had the longest time to flowering, as well as longer duration of photoperiod sensitivity phases under LD and SD. Daba et al (2015 , 2016 ) reported that ICCV 96029 (N1) and FLIP98-142C (N2) flowered the earliest; ICC 15294 (I1), ICC 8621 (I2), ILC 1867 (I3), and ICC 8855 (I4) flowered intermediate and CDC Frontier (S2) and CDC Corinne (S1) flowered the latest under a combination of temperature and photoperiod in the growth chamber conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The two high yielding accessions developed and released by the Crop Development Centre, University of Saskatchewan [CDC Corinne (S1) and CDC Frontier (S2)] ( Warkentin et al, 2005 ; Tar’an et al, 2009 ) had the longest time to flowering, as well as longer duration of photoperiod sensitivity phases under LD and SD. Daba et al (2015 , 2016 ) reported that ICCV 96029 (N1) and FLIP98-142C (N2) flowered the earliest; ICC 15294 (I1), ICC 8621 (I2), ILC 1867 (I3), and ICC 8855 (I4) flowered intermediate and CDC Frontier (S2) and CDC Corinne (S1) flowered the latest under a combination of temperature and photoperiod in the growth chamber conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, those sown on SD4 emerged when days were starting to lengthen after the winter solstice on 21 June. Chickpea can be photoperiod insensitive/day length neutral, intermediate sensitive or highly sensitive to day length [ 24 ]. The genotypes used in this study are all photoperiod sensitive as their ability to switch from the vegetative phase to the reproductive phase was affected by sowing time, with longer days reducing the thermal time target, thus requiring fewer GDD to flower.…”
Section: Discussionmentioning
confidence: 99%
“…Matching crop phenology to environment is critical for stress adaptation and crop yield 7 , hence the importance of accurate prediction of flowering time. Based on experimental studies 8,9 , crop simulation models including the Agriculture Production Systems Simulator (APSIM) and Decision Support System for Agrotechnology Transfer (DSSAT) 1013 , model chickpea phenology as a function of temperature and photoperiod. However, prediction of flowering time based on these two parameters is relatively poor 14–16 , suggesting other drivers of crop development may have been overlooked.…”
Section: Introductionmentioning
confidence: 99%